Critical remarks on the International Court of Justice’s interpretation of Article 3(g) of the “Definition of Aggression”(UNGA Resolution 3314/1974) - Taciano Scheidt Zimmermann (Revista Direito GV)
Abstract The purpose of this paper is to examine whether and to what extent the Article 3(g) of the General Assembly Definition of Aggression (Resolution 3314/1974 XXIX) can be interpreted using the case-law of the International Court of Justice. Three judgments delivered by the Court are analyzed: Military and Paramilitary Activities in and against Nicaragua (Nicaragua v. United States of America), Armed Activities on the Territory of the Congo (Democratic Republic of the Congo v. Uganda) and Application of the Convention on the Prevention and Punishment of the Crime of Genocide (Bosnia and Herzegovina v. Serbia and Montenegro). Special attention is given to the connection between international norms on the use of force and the law of international responsibility, as well as to the meaning and status attributed by the Court to the expressions “sending” and “substantial involvement,” both present in Article 3(g).